Targeting c-Met in the treatment of urologic neoplasms: Current status and challenges - Su, Pengxiao; Zhang, Ming; Kang, Xin (Frontiers in Oncology, 2023)
At present, studies have found that c-Met is mainly involved in epithelial-mesenchymal transition (EMT) of tumor tissues in urologic neoplasms. Hepatocyte growth factor (HGF) combined with c-Met promotes the mitosis of tumor cells, and then induces motility, angiogenesis, migration, invasion and drug resistance. Therefore, c-Met targeting therapy may have great potential in urologic neoplasms. Many strategies targeting c-Met have been widely used in the study of urologic neoplasms. Although the use of targeting c-Met therapy has a strong biological basis for the treatment of urologic neoplasms, the results of current clinical trials have not yielded significant results. To promote the application of c-Met targeting drugs in the clinical treatment of urologic neoplasms, it is very important to study the detailed mechanism of c-Met in urologic neoplasms and innovate c-Met targeted drugs. This paper firstly discussed the value of c-Met targeted therapy in urologic neoplasms, then summarized the related research progress, and finally explored the potential targets related to the HGF/c-Met signaling pathway. It may provide a new concept for the treatment of middle and late urologic neoplasms.